Prevention of migraine in the pill-free interval of combined oral contraceptives: A double-blind, placebo-controlled pilot study using natural oestrogen supplements. Issue 1 (1st January 2002) - MacGregor, E Anne; Hackshaw, Allan
Abstract : Context: Migraine in the pill-free interval of combined oral contraceptives is reported by many women, but there is little published information on possible mechanisms and treatments. Objective: To determine whether the use of natural oestrogen patches affected the occurrence and severity of migraine during the pill-free interval. Design: A double-blind, placebo-controlled, randomised, crossover study. Setting: The City of London Migraine Clinic. Participants: Fourteen women with migraine during the pill-free interval. Interventions: 50 μg oestradiol patches (Evorel™) used during the pill-free interval for two cycles versus placebo for two cycles (total four cycles). Main outcome measures: Number of pill-free intervals (zero, one or two) during which migraine occurred; number of days of migraine; severity of migraine; number of days of migraine accompanied by nausea, vomiting and/or photophobia. Results: Complete data were available for 12 women and for two cycles for one woman. Use of 50 μg oestrogen patches during the pill-free interval showed a trend towards reducing the frequency and severity of migraine. Discussion: These results were not as good as expected. However, we had originally aimed for 20 eligible women to participate in the trial, but only 14 were recruited and only 12 completed the study with full data for analysis. Conclusion: The results of this pilot study suggest that use of 50 μg oestrogen patches during the pill-free interval may reduce the frequency and severity of migraine at that time. This study should be repeated with larger numbers of women and a higher dose of oestrogen.